Cognitive Neuroscience Robotics B Analytic Approaches to Human Understanding - Kasaki, Masashi; Ishiguro, Hiroshi; Asada, Minoru; Osaka, Mariko; Fujikado, Takashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
Cognitive Neuroscience Robotics is the first introductory book on this new interdisciplinary area. This book consists of two volumes, the first of which, Synthetic Approaches to Human Understanding, advances human understanding from a robotics or engineering point of view. The second, Analytic Approaches to Human Understanding, addresses related subjects in cognitive science and neuroscience. These two volumes are intended to complement each other in order to more comprehensively investigate human cognitive functions, to develop human-friendly information and robot technology (IRT) systems, and to understand what kind of beings we humans are. Volume B describes to what extent cognitive science and neuroscience have revealed the underlying mechanism of human cognition, and investigates how development of neural engineering and advances in other disciplines could lead to deep understanding of human cognition.
Perceptual and Cognitive Processes in Human Behavior -- Emotion -- Working Memory as a Basis of Consciousness -- Primate Social Behavior: Understanding the social relationships of Japanese macaques -- Adaptation and psychological disorders -- Mechanisms of Pain -- Magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) -- Advances in Neuroimaging Techniques with PET -- Movement disorders and motor cortex stimulation -- Brain Machine-Interfaces for Sensory Systems -- Brain Machine-Interfaces for Motor and Communication Control -- Norms and Games as Integrating Components of Social Organizations. .
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Computational intelligence; Neurosciences; Control, Robotics, Automation; Artificial Intelligence; Computational Intelligence; Neuroscience